Utilization of fish protein hydrolysate in prepared diets for pacu, Piaractus mesopotamicus, larvae - Macedo-Viegas, Elisabete Maria [UNESP]; Portella, Maria Célia; Carneiro, Dalton José [UNESP] (Taylor & Francis, 2003)
Growth and survival rates of pacu, Piaractus mesopotamicus, larvae fed prepared diets containing different animal protein sources were evaluated. Four diets with the same level of crude protein (CP) (36%) and calories (4.02 kcal gross energy/g of diet) were fed to the larvae. Diets were formulated to contain one of four protein sources: (1) fish meal (FM), (2) tilapia residue silage (TS), (3) protein hydrolysate from tilapia residue (HT), and (4) eviscerated tilapia residue (HET). Larvae were fed Artemia nauplii for six days, prior to the start of the study, and the prepared diet was supplied from day 7 until the study concluded. Variance analysis showed no significant differences (P > 0.05) for survival rates and larval final lengths among treatments. However, final average weights were significantly different (P < 0.05 for larvae fed FM and HT. Average survival rates were relatively high and ranged from 68.1% to 73.9%. After the live food was replaced by prepared diets, no larval growth was observed for any treatment. Fish protein hydrolysate (HT and HET) and fish silage showed potential to be used as ingredients in the diet of pacu larvae. However, hydrolysate inclusion levels, processing methods to minimize nutrient lixiviation, and the best moment to replace live food with an inert diet (weaning) need further investigation. © 2003 by The Haworth Press, Inc. All rights reserved.
Keywords: Diets; Fish protein hydrolysate; Larvae; Pacu; Piaractus mesopotamicus; artificial diet; fish culture; food organism; growth rate; larviculture; survival; Animalia; Artemia; Piaractus; Tilapia